Effect of metal-cation antacids on the pharmacokinetics of 1200 mg raltegravir. (27th September 2016) - Krishna, Rajesh; East, Lilly; Larson, Patrick; Valiathan, Chandni; Butterfield, Kristin; Teng, Yang; Hernandez-Illas, Martha
Abstract: Objectives: Raltegravir is a human immunodeficiency virus (HIV)-1 integrase strand transfer inhibitor currently marketed at a dose of 400 mg twice daily (BID). Raltegravir for once-daily regimen (QD) at a dose of 1200 mg is under development. The effect of calcium carbonate and magnesium/aluminium hydroxide antacids on the pharmacokinetics of a 1200 mg dose of raltegravir was assessed in this study. Methods: An open-label, four-period, four-treatment, fixed-sequence study in 20 HIV-infected patients was performed. Patients needed to be on raltegravir as part of a stable treatment regimen for HIV, and upon entry into the trial received 5 days of 1200 mg raltegravir as pretreatment, before they entered the four-period study: 1200 mg of raltegravir alone (period 1), calcium carbonate antacid as TUMS® Ultra Strength (US) 1000 and 1200 mg raltegravir given concomitantly (Period 2), magnesium/aluminium hydroxide antacid as 20 ml MAALOX® Maximum Strength substitute MS given 12 h after administration of 1200 mg raltegravir (period 3), and calcium carbonate antacid as TUMS® US 1000 given 12 h after administration of 1200 mg raltegravir (period 4). Patients received their dose of 1200 mg QD raltegravir during the intervals between periods to re-establish steady state. AUC0–24, C 24, C max and T max were calculated from the individual plasma concentrations of 1200 mg QD raltegravir after administration alone or with a calcium carbonate antacid or with a staggered dose of a calcium carbonate antacid or magnesium/aluminium hydroxide antacid. Adverse events, in addition to laboratory safety tests (haematology, serum chemistry and urinalysis), 12-lead electrocardiograms and vital signs were assessed. Key findings: All treatments were well tolerated in the study. Metal-cation antacids variably affected the pharmacokinetics of 1200 mg QD raltegravir. When calcium carbonate antacid was given with 1200 mg raltegravir concomitantly, the geometric mean ratio (GMR) and its associated 90% confidence interval (90% CI) for AUC0–24, C max and C 24 h were 0.28 (0.24, 0.32), 0.26 (0.21, 0.32) and 0.52 (0.45, 0.61), respectively. When calcium carbonate antacid and magnesium/aluminium hydroxide were given 12 h after raltegravir 1200 mg QD dosing, the GMR (90% CI) values for AUC0–24 and C max were 0.90 (0.80, 1.03), 0.98 (0.81, 1.17), and 0.86 (0.73, 1.03), 0.86 (0.65, 1.15), respectively. However, significant reduction in the trough concentrations of raltegravir was observed: C 24 h 0.43 (0.36, 0.51) in the presence of calcium carbonate antacids and 0.42 (0.34, 0.52) in presence of magnesium/aluminium hydroxide, respectively. Conclusions: Overall, the use of metal-cation antacids with 1200 mg QD raltegravir is not recommended.